2016
DOI: 10.1055/s-0036-1592117
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Hearing Aid Benefits of Digital Hearing Aid Use (BTE) from Six Months to Two Years

Abstract: Introduction  For many reasons, it is important for audiologists and consumers to document improvement and benefit from amplification device at various stages of uses of amplification device. Professional are also interested to see the impact of amplification device on the consumer's auditory performance at different stages i.e. immediately after fitting and over several months of use. Objective  The objective of the study was to measure the hearing aid benefit following 6 months – 1-year usage, 1 year – 1.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Thus, such a methodology proposed by the authors could be one of the core applications for HA fitting. Moreover, as indicated in some reports, a more extended observation of the HA use benefit should be considered [51]. Undoubtedly, implementing the application in mobile form on a smartphone is also a future development area for the method.…”
Section: Conclusion and Future Research Aspectsmentioning
confidence: 95%
“…Thus, such a methodology proposed by the authors could be one of the core applications for HA fitting. Moreover, as indicated in some reports, a more extended observation of the HA use benefit should be considered [51]. Undoubtedly, implementing the application in mobile form on a smartphone is also a future development area for the method.…”
Section: Conclusion and Future Research Aspectsmentioning
confidence: 95%
“…Real-world data have high ecological validity (Verma et al 2017;Hicks et al 2019) but also lack control for when, where, and how much data are logged. In that sense, a limitation of this study is that some participants collected less data than others.…”
Section: Limitationsmentioning
confidence: 99%
“… Karawani et al (2018a) showed that satisfaction with HAs increased over the course of 6 months. Verma et al (2017) measured subjective benefits of the use of HAs at 6 months, 1 year, 1.5 years, and 2 years using the Hearing Aid Benefit Questionnaire, and showed high satisfaction scores in aided situations. However, benefits varied depending on whether the listening background was quiet, noisy or music.…”
Section: Introductionmentioning
confidence: 99%